Una presentación rara de Neurocisticercosis con mioclonías - Marta Matos Pereira; Tiago Mendes (Sociedade Galega de Medicina Interna, 2022)
Neurocysticercosis (NCC) is caused by the infection of the central nervous system (CNS) by the larval stage of Taenia solium, with higher prevalence in developing countries. Seizures (more frequently partial seizures) and headaches are the most common clinical manifestations of NCC. Its diagnosis requires compatible exposure history, clinical manifestations and imaging results. We report the case of a 59 year-old man with NCC presenting with myoclonus, which is a rarer form of presentation of this disease.